Return to Sport After Articular Cartilage Repair in Athletes' Knees: A Systematic Review - Campbell, Andrew B; Pineda, Miguel; Harris, Joshua D; Flanigan, David C (Arthroscopy, 2016)
To perform a systematic review of cartilage repair in athletes' knees to (1) determine which (if any) of the most commonly implemented surgical techniques help athletes return to competition, (2) identify which patient- or defect-specific characteristics significantly affect return to sport, and (3) evaluate the methodologic quality of available literature. A systematic review of multiple databases was performed. Return to preinjury level of sport was defined as the ability to play in the same or greater level (i.e., league or division) of competition after surgery. Study methodologic quality for all studies analyzed in this review was evaluated with the Coleman Methodology Score. Systematic review of 1,278 abstracts identified 20 level I-IV studies for inclusion but only 1 randomized controlled trial. Twenty studies (1,117 subjects) were included. Subjects (n = 970) underwent 1 of 4 surgeries (microfracture [n = 529], autologous chondrocyte implantation [ACI, n = 259], osteochondral autograft [n = 139], or osteochondral allograft [n = 43]), and 147 were control patients. The rate of return to sports was greatest after osteochondral autograft transplantation (89%) followed by osteochondral allograft, ACI, and microfracture (88%, 84%, and 75%, respectively). Osteochondral autograft transplantation and ACI had statistically significantly greater rates of return to sports compared with microfracture (P < .001, P < .01; Fisher exact test). Athletes may return to sports participation after microfracture, ACI, osteochondral autograft, or osteochondral allograft, but microfracture patients were least likely to return to sports. The athletes who had a better prognosis after surgery were younger, had a shorter preoperative duration of symptoms, underwent no previous surgical interventions, participated in a more rigorous rehabilitation protocol, and had smaller cartilage defects. Level IV, systematic review of Level I-IV studies.